Contributionà l'étude de la qualité physico-chimique et bactériologique des eaux d'une zone humide de la wilaya d'El-Oued (cas de lac Ayata) - BIA Ouisem; MEISA Aouatef; MERZOUG Fatima; MESBAHI Salima (جامعة الوادي university of eloued, 2015)
Our work focused on the study of physical-chemical and bacteriological quality of Ayata lake water based on the Algerian standards and W.H.O. The analysis we have made are physico-chemical analysis (pH, TDS, Ca , Iron Residue Sec . etc.) and bacteriological tests (fecal coliforms, fecal streptococi .) of lake water studied. The analysis of the water from this lake rise they are troubled water, salted with an electrical conductivity of 9760 µS /cm, the pH is generaly alkaline. The water is charged into soluble salts with a calcium chloride-facies. Concerning bacteriological analysis, the results showed the presence of fecal contamination indicators such as faecal coliforms and faecal streptococi, sulphite-reducing Clostridium. With this results, we concluded that he lake water Ayata is unfit for human consumption.
biochimie
Keywords: physico-chemical analysis; bacteriological analysis; wetland; lake Ayata; water quality standards.